1991
DOI: 10.1093/oxfordjournals.aje.a116129
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Epidemiology of Postmenopausal Breast Cancer in Western New York

Abstract: The authors studied 439 postmenopausal breast cancer cases, identified in hospitals throughout western New York, with an interview schedule that considered frequency and amount ingested of 172 foods and provided data for an estimate of total calories ingested. These were compared with age-matched controls comprising a random sample of the same communities as the cases. The extensive interviews, requiring 2.0 hours on average to administer, also covered alcohol ingestion, Quetelet index, and a wide variety of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(70 citation statements)
references
References 0 publications
6
64
0
Order By: Relevance
“…In our study, supplemental vitamin C intake was not associated with the risk of breast cancer, which is in agreement with results of other epidemiological studies (Graham et al, 1991;Shibata et al, 1992Hunter et al, 1993. Rohan et al (1993) reported a 40-50% increase in the risk of breast cancer in association with the intake of more than 250 mg day-' vitamin C supplements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, supplemental vitamin C intake was not associated with the risk of breast cancer, which is in agreement with results of other epidemiological studies (Graham et al, 1991;Shibata et al, 1992Hunter et al, 1993. Rohan et al (1993) reported a 40-50% increase in the risk of breast cancer in association with the intake of more than 250 mg day-' vitamin C supplements.…”
Section: Discussionsupporting
confidence: 93%
“…Some case-control studies showed a decrease in breast cancer risk with increased intake of the (pro)vitamins (Katsouyanni et al, 1988;Howe et al, 1990; Graham et al, 1991;Lee et al, 1991;Zaridze et al, 1991) and fibre (Iscovich et al, 1989;Howe et al, 1990;Van 't Veer et al, 1990; Graham et al, 1991;Baghurst and Rohan, 1994), whereas other case-control studies showed the opposite for (pro)vitamins (Toniolo et al, 1989;Ewertz and Gill, 1990;Richardson et al, 1991) and fibre (Katsouyanni et al, 1988;Ingram et al, 1991). Mostly negative non-significant associations between (pro)vitamin intake and the risk of breast cancer have been found in the few prospective cohort studies that have been conducted so far (Paganini-Hill et al, 1987;Graham et al, 1992;Hunter et al, 1993;Rohan et al, 1993).…”
mentioning
confidence: 99%
“…The relative risk of breast cancer comparing the highest with the lowest category of intake was extracted from each study. Relative risks and CIs were calculated for three studies (Graham et al, 1982(Graham et al, , 1991Yuan et al, 1995) and confidence intervals were calculated for five studies (Hirayama, 1978;Kinlen, 1982;Levi et al, 1993;Landa et al, 1994;Toniolo et al, 1994) by cell frequencies shown in the data or standard error values (Fleiss, 1981), and are thus unadjusted for other variables. If the risk of breast cancer associated with the dietary variables was expressed in more than one way, the estimate extracted from the study was the one that reflected the greatest degree of controlling for confounders (i.e.…”
Section: Extraction and Classification Of Datamentioning
confidence: 99%
“…[20][21][22] Furthermore, a series of animal studies reported that the inhibitory effect of dietary fiber on the promotion of mammary carcinogenesis was not only through modulating the level of circulating 17b-estradiol, 8,23,24 but a potential effect of bioactive compounds with anticancer properties such as antioxidants, phytoestrogens, phytic acid and protease inhibitors in dietary fiber was also discussed. [25][26][27][28] Epidemiological studies have evaluated intake of total fiber in relation to overall breast cancer risk in 10 cohorts, [29][30][31][32][33][34][35][36][37][38] in a metaanalysis of 12 older case-control studies, 39 and 8 more recent case-control studies, [40][41][42][43][44][45][46][47] but results are not consistent. To date, only 2 prospective studies with a limited number of cases have reported the association between intake of fiber and the risk of postmenopausal breast cancer defined by ER/PR status.…”
mentioning
confidence: 99%